Attitudes towards working wives in an urban setting - Ventura, Elizabeth R.; Koehler, Gerda; Udarde, Margaret; Agbing, Lou (Philippine Journal of Psychology, 1979)
The present study utilized a 2x2 factorial design to investigate the effects of civil status and sex differences on attitudes toward working wives. It was hypothesized that compared to male respondents, female respondents would show more positive attitudes toward working wives. The study further explored the effect of civil status on attitudes and its possible interaction with sex. Sixty graduate students equally divided according to sex and civil status were administered a twenty-item Likert-type scale. An analysis of variance revealed that the females had a more positive attitude concerning female employment than males (p<.01) while civil status did not appear to be a significant variable. No interaction effects were obtained.